BLENDED LEARNING AND IMPROVING QUALITY OF LEARNING (POST PANDEMIC IMPLEMENTATION IN MAN 1 SRAGEN, CENTRAL JAVA) - Noor, Triana Rosalina; Susanti, Winda (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2023)
This study aims to provide an overview and analyze blended learning-based learning to improve the quality of learning at MAN 1 Sragen after the pandemic by using a qualitative-case study as paradigm. This is because blended learning is a form of learning innovation that combines several activities to make learning more flexible and efficient. Research data was collected through interviews, observations and documents which were then analyzed narratively through a process of data condensation, data presentation and conclusions. Interviews were conducted with the principal, vice principal of curriculum, teachers and students. The research results show that the implementation of blended learning-based learning at MAN 1 Sragen goes through four main processes, namely planning, organizing, implementing and evaluating. At the planning level, the school prepares curriculum guidelines that accommodate blended learning. In the organizing process, the school arranges human resources along with the main tasks and functions that must be carried out referring to the indicators of success to be achieved. In the learning evaluation process, the school carries out routine quantitative and qualitative reviews. The quality of blended learning-based learning is carried out by paying attention to three quality processes, namely input, output and outcome. Apart from that, blended learning based learning at MAN 1 Sragen also refers to several principles such as conformity with community needs, interest from school components in the integration of technology in learning, implementation of effectiveness and efficiency and implementation of productive learning that is able to produce good learning. quality. Blended learning-based learning makes the learning process more active, increases student independence and is able to strengthen students' learning experiences.